Diagnosis of feline infectious peritonitis by immunohistochemistry and histopathology methods: a case report based on diagnostic approach - Mehmet Burak Ateş; Gökhan Akçakavak; Zeynep Çelik; Özgür Özdemir (Eurasian Journal of Veterinary Sciences)
Aim: In this study the case of feline infectious peritonitis (FIP) has been identified as histopathological and immunohistochemical (IHC) in a 6-month-old male domestic shorthair cat. In necropsy, the abdominal cavity contained a significant volume of yellow liquid and granular fibrinous exudate was seen on the liver, serosa of intestines, and peritoneum. Microscopically, inflammatory cell infiltration and fibrin exudation, consisting mainly of macrophage, lymphocyte and plasma cells, were determined around small and medium-sized vessels in the tunica serosa layer of the intestines. Many granulomatous foci of various sizes, with or without necrosis, were found in the liver, spread to the parenchyma. In methyl green pyronin staining, plasma cells were found to be the majority of the inflammatory cells present in lesions. In IHC staining with specific antibodies against the agent, immunopositivity was obtained in granulomatous lesions in the serosa layer of the intestines and less frequently in the cytoplasm of mononuclear cells in the lamina propria. Immunoreactivity was detected in the cytoplasm of macrophages in the liver, around both pyrogranulomas and granulomas. It was concluded that this case of FIP, when all findings are evaluated together, may have started as a dry form, and turned into a wet form in the terminal period.